2014
DOI: 10.1002/oby.20747
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of “healthy beginnings” an early childhood intervention to prevent obesity

Abstract: Objective: To determine the costs and cost-effectiveness of an early childhood home visiting program delivered to families in socio-economically disadvantaged areas of Sydney, Australia during 2007-2010. Methods: Economic evaluation of a randomized controlled trial, the healthy beginnings (HB) trial, from the perspective of the health funder. Intervention resources were determined from local health district records in 2012 $AUD. Health-care resource utilization was determined through patient-level data linkage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
76
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 38 publications
(77 citation statements)
references
References 21 publications
0
76
1
Order By: Relevance
“…This early intervention was effective in reducing children’s body mass index and reducing TV viewing at age 2 years [22], as well as improving infant feeding practices including breastfeeding [25]. However, the economic evaluation of the HBT showed that the early obesity prevention through home visits was only moderately cost-effective, with the cost of home visiting potentially limiting the level of population reach [26]. Hence, other new, low cost and high uptake approaches need to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…This early intervention was effective in reducing children’s body mass index and reducing TV viewing at age 2 years [22], as well as improving infant feeding practices including breastfeeding [25]. However, the economic evaluation of the HBT showed that the early obesity prevention through home visits was only moderately cost-effective, with the cost of home visiting potentially limiting the level of population reach [26]. Hence, other new, low cost and high uptake approaches need to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 369 children were recruited to the economic sub‐study. Consent for health‐care data linkage was obtained for 363 participants; of these, 13 did not have successful linkage to either Medicare or CHeRel, leaving 350 participants (95%) for analysis . Child, maternal and household characteristics of the participants at baseline are shown in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Socio‐demographic characteristics were collected prior to birth or at the first post‐natal visit, using standard questions from the New South Wales (NSW) Population Health Survey . As there were no differences in health‐care costs or health‐care utilisation (adjusted incidence rate ratio = 0.97, P = 0.24) between the intervention and control participants, data were combined from both arms of the trial in the present analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Trial‐based economic evaluations consider the costs and outcomes within the randomized controlled trial's (RCT's) observation time . This provides useful information on the more immediate cost‐effectiveness of interventions, often reporting findings related to outcomes in the shorter‐term such as cost per unit of weight gain or body mass index (BMI) point avoided during the study timeframe or follow‐up period . Whilst these types of evaluations are well suited to inform the technical efficiency of studies (i.e how to best maximize outcomes with a given set of resources), they do not provide information on how to best allocate those resources (ie, allocative efficiency).…”
Section: Introductionmentioning
confidence: 99%